KUALITAS FISIK DAGING BROILER DI PASAR TRADISIONAL KOTA BANDAR LAMPUNG - Aji Ardiansyah; Rr. Riyanti; Dian Septinova; Khaira Nova (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2021)
Broiler meat is one of the most common sources of animal protein consumed by Indonesians. This study aimed to determine the physical quality of broiler meat including pH value, water holding capacity, and cooking losses of broiler meat in the traditional market of Bandar Lampung city. This research was conducted in December 2019–January 2020. This research used a survey method using 79 samples of breast broiler meat. The sample was from 13 traditional markets in the city of Bandar Lampung (Rajabasa market, Untung market, SMEP market, Koga market, Way Kandis market, Way Halim market, Tugu market, Tamin market, Kangkung market, Cimeng market, Lempasing market, Gudang Lelang market, and Panjang market). The variables observed in this study included degree of Power of Hydrogen (pH), water holding capacity (WHC), and cooking losses. The results of this study indicated that the highest pH value (6.04) was from the Lempasing market, the lowest pH value (6.138) was from Gudang Lelang market, the highest WHC value was from the Lempasing market which was 58.13%, the lowest WHC value was from Way Kandis market which was 52.76%, the highest cooking loss value was obtained from the SMEP market which was 31.48%, and the lowest cooking loss value was obtained from the Rajabasa market which was 27.29%. It can be concluded that the pH value and cooking loss were still normal with an average range of 6.138– 6.304 and 27.29–31.48%, respectively, while the average range of water holding capacity was in high category (52.76–58.13). Keywords: Broiler, Cooking loss, pH, Traditional market, Water holding capacity